Menyoal Tanggung Jawab Negara dalam Kepailitan BUMN-Persero - Windu Natalia, Siska; Darmawan Hutag, Henry (Fakultas Hukum, Universitas Islam Balitar, 2024)
This study focuses on analyzing the bankruptcy of state-owned enterprises (BUMN Persero), highlighting the limits of state liability in the bankruptcy petition of PT. Garuda Indonesia. This research is important as it explores the research gap regarding the relationship between separated state assets and state liability in BUMN bankruptcies. The objective is to thoroughly examine the boundaries of state responsibility in the context of BUMN bankruptcy, specifically in the case of PT. Garuda Indonesia. The methodology employed is normative legal research, with secondary data analysis from various relevant regulations, such as the State Finance Law, the BUMN Law, the Bankruptcy Law, and the Company Law. The key findings reveal that the transformation of state assets into BUMN assets severs the burden and liability of the state as a public legal entity, making PT. Garuda Indonesia's bankruptcy is a business loss rather than a fiscal risk or state loss. The implication is that the state is only liable to the extent of its shareholding.